Health-related quality of life of the parents of children hospitalized due to acute rotavirus infection: a cross-sectional study in Latvia - Gunta Laizane; Anda Kivite; Inese Stars; Marita Cikovska; Ilze Grope; Dace Gardovska (BMC, 2018)
Abstract Background Rotavirus is the leading cause of severe diarrhea in young children and infants worldwide, representing a heavy public health burden. Limited information is available regarding the impact of rotavirus gastroenteritis on the quality of life of affected children and their families. The objectives of study were to estimate the impact of rotavirus infection on health-related quality of life (HRQL), to assess the social and emotional effects on the families of affected children. Methods This study enrolled all (n = 527) RotaStrip®-positive (with further PCR detection) cases (0-18 years of age) hospitalized from April 2013 to December 2015 and their caregivers. A questionnaire comprising clinical (filled-in by the medical staff) and social (filled by the caregivers) sections was completed per child. Results Main indicators of emotional burden reported by caregivers were compassion (reported as severe/very severe by 91.1% of parents), worry (85.2%), stress/anxiety (68.0%). Regarding social burden, 79.3% of caregivers reported the need to introduce changes into their daily routine due to rotavirus infection of their child. Regarding economic burden, 55.1% of parents needed to take days off work because of their child's sickness, and 76.1% of parents reported additional expenditures in the family's budget. Objective measures of their child's health status were not associated with HRQL of the family, as were the parent's subjective evaluation of their child's health and some sociodemographic factors. Parents were significantly more worried if their child was tearful (p = 0.006) or irritable (p < 0.001). Parents were more stressful/anxious if their child had a fever (p = 0.003), was tearful (p < 0.001), or was irritable (p < 0.001). Changes in parents' daily routines were more often reported if the child had a fever (p = 0.02) or insufficient fluid intake (p = 0.04). Conclusion Objective health status of the child did not influence the emotional, social or economic burden, whereas the parents' subjective perception of the child's health status and sociodemographic characteristics, were influential. A better understanding of how acute episodes affect the child and family, will help to ease parental fears and advise parents on the characteristics of rotavirus infection and the optimal care of an infected child.